2019
DOI: 10.7717/peerj.7800
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and gene transcription assays to assess responses of mussels to environmental changes

Abstract: Coastal regions worldwide face increasing management concerns due to natural and anthropogenic forces that have the potential to significantly degrade nearshore marine resources. The goal of our study was to develop and test a monitoring strategy for nearshore marine ecosystems in remote areas that are not readily accessible for sampling. Mussel species have been used extensively to assess ecosystem vulnerability to multiple, interacting stressors. We sampled bay mussels (Mytilus trossulus) in 2015 and 2016 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Although differences in Pacific razor clams were identified among locations, the variances of physiological and gene transcription values within populations were relatively low when compared to data on bay mussels (Mytilus trossulus) collected from the same general locations in the two parks (Counihan et al, 2019). We suspect this may be due in part to lower variability in physical attributes (such as temperature and wave action) of razor clam habitat.…”
Section: Nmds Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Although differences in Pacific razor clams were identified among locations, the variances of physiological and gene transcription values within populations were relatively low when compared to data on bay mussels (Mytilus trossulus) collected from the same general locations in the two parks (Counihan et al, 2019). We suspect this may be due in part to lower variability in physical attributes (such as temperature and wave action) of razor clam habitat.…”
Section: Nmds Resultsmentioning
confidence: 73%
“…This study was conducted concurrently with a similar study on mussels, recently reported by Counihan et al (2019). Study areas (Lake Clark National Park and Preserve, LACL and Katmai National Park and Preserve, KATM) were the same although the specific collection substrates within each park varied for mussels (protected mixed-sediment) vs. razor clams (exposed soft sediment).…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations